TGFβ1 secreted by cancer-associated fibroblasts induces epithelial-mesenchymal transition of bladder cancer cells through lncRNA-ZEB2NAT - Zhuang, Junlong; Lu, Qun; Shen, Bing; Huang, Xiaojing; Shen, Lan; Zheng, Xi; Huang, Ruimin; Yan, Jun; Guo, Hongqian (Scientific reports, 2015)
Urinary bladder cancer (UBC) patients at muscle invasive stage have poor clinical outcome, due to high propensity for metastasis. Cancer-associated fibroblasts (CAFs), one of the principal constituents of the tumor stroma, play an important role in tumor development. However, it is unclear whether CAFs from UBC induce cell invasion and which signaling pathway is involved. Herein, we found that conditional medium from UBC CAFs (CAF-CM) enhanced the invasion of UBC cells. CAF-CM induced the epithelial-mesenchymal transition (EMT) by regulating expression levels of EMT-associated markers in UBC cells. Higher concentration of TGFβ1 in CAF-CM, comparing with the CM from adjacent normal fibroblast, led to phosphorylation of Smad2 in UBC cells. Additionally, inhibition of TGFβ1 signaling decreased the EMT-associated gene expression and cancer cell invasion. Interestingly, a long non-coding RNA, ZEB2NAT, was demonstrated to be essential for this TGFβ1-dependent process. ZEB2NAT depletion reversed CAF-CM-induced EMT and invasion of cancer cells, as well as reduced the ZEB2 protein level. Consistently, TGFβ1 mRNA expression is positively correlated with ZEB2NAT transcript and ZEB2 protein levels in human bladder cancer specimens. Our data revealed a novel mechanism that CAFs induces EMT and invasion of human UBC cells through the TGFβ1-ZEB2NAT-ZEB2 axis.